Assessing the Life-cycle Greenhouse gas (GHG) Emissions of Renewable and Fossil Fuel Energy Sources in Iran - Gholamreza Nabi Bid Hendi; Ali Daryabeigi Zand; Maryam Rabiee Abyaneh (Environmental Energy and Economic Research)
Renewable power generation is known as a low emission energy source. However, it is extremely important to analyze the greenhouse gas (GHG) emissions of renewable energy power stations along the entire life-cycle to broaden the concept of sustainability to an environmental and economic point of view. The main objective of this study was assessing and comparing the GHG emissions within the life-cycle of solar and gas power generation in Iran. A further objective was to evaluate the external costs associated with carbon emissions. The life-cycle inventory was first analyzed. The output emissions inventoried in the study were carbon dioxide (CO2). Then the CO2 emission and social cost of carbon during every process in solar and gas technologies were calculated by energy and environment software. Gas power plants are found to have a life-cycle CO2 emission of 658 g-CO2/kWh, which is comparatively higher than solar power life cycles (5.9 g-CO2/kWh). Life-cycle CO2 emissions from solar and gas power generation systems, imposes 70.8 and 2883.6 million US dollars/year to compensate its social effects. Results of the present study showed that the solar power generation is the environmentally-friendly form of producing electricity when compared with gas power technology in terms of life-cycle CO2 emissions. This makes solar power as promising solution to the Iran's cleaner power transition.